1967
DOI: 10.4141/cjps67-035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stem Nematode Infestation on Bacterial Wilt Reaction and Forage Yield of Alfalfa Varieties

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nematodes can alter the performance of arthropods and other plant pathogens on shared host plants (Hawn and Hanna 1967 ; Wondafrash et al 2013 ). Here, we found that stem nematodes increased aphid abundance on alfalfa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nematodes can alter the performance of arthropods and other plant pathogens on shared host plants (Hawn and Hanna 1967 ; Wondafrash et al 2013 ). Here, we found that stem nematodes increased aphid abundance on alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the studies that tested the effects of root-feeding nematodes on aphid abundance aboveground (examples in McCarville et al 2012 ; Wondafrash et al 2013 ). One of a few studies examining stem nematodes investigated the impact of stem nematodes on bacterial wilt ( Corynebacterium insidiosum ) and found that nematodes also can increase the susceptibility of alfalfa varieties to this bacterium (Hawn and Hanna 1967 ). An example on melon plants shows that other plant pathogens also can enhance aphid abundance (Moran 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the nematode could transmit the bacteria, as numerous bacterial cells were observed on the nematode after artificial inoculation. This nematode was able to decrease bacterial wilt resistance in lucerne by causing physiological or biochemical change, but not in all cultivars, (Hawn and Hanna, 1967).…”
Section: Conditions Favouring Disease Developmentmentioning
confidence: 92%
“…This effect was found independent of whether the bacteria or the nematode came first (Griffin and Hunt, 1972). This nematode was able to decrease bacterial wilt resistance in lucerne by causing physiological or biochemical change, but not in all cultivars, (Hawn and Hanna, 1967). Dissemination of C. michiganensis subsp.…”
Section: Conditions Favouring Disease Developmentmentioning
confidence: 95%
See 1 more Smart Citation